DETECTION OF THE MULTI-TEMPORAL DYNAMICS OF THE VEGETATION COVERS IN THE ALGERIAN STEPPE BY REMOTE SENSING CASE OF THE KESDIRE ZONE (NAAMA WILAYA - Nadjla Bentekhici; Ahmed Zegrar; Sid-Ahmed Bellal (Acta Geobalcanica, 2019)
The Algerian steppe is very affected by the ecological and climatic imbalance; the degradation of the natural environment is currently a serious problem following silting, wind erosion, overgrazing and clearing. The extent of degradation in the semi arid zone (commune of Kesdire in Naama wilaya) has led to a significant regression of the vegetation cover, requires a better understanding in order to see how to fight against this plague and propose adequate facilities. Through this work, we have tried to show, on the one hand, the potential of using remote sensing for the detection of the dynamics of the steppe cover and its spatiotemporal evolution from the treatments carried out on Landsat 5 satellite images and 8 (March 1987 and March 2015). On the other hand, to provide decision-makers with information on the state of the vegetation cover in this area. The method used is based on the interpretation of the treatments (calculations of MSAVI vegetation indices and soil brightness IB) on Landsat satellite images, these digital treatments made it possible to analyze the multi-temporal dynamics of the vegetation cover and identifying areas of degradation within 28 years. The results of our study show that the state of the vegetation cover and its evolution seem alarming, our study area lost 22.22 % of its natural vegetation during the last quarter of the century. This change informs about the different changes that the municipality of Kesdire has experienced.